Salud financiera de las empresas socialmente responsables utilizando Z-Score de Altman Financial health of socially responsible companies using z-score de altman: http://repositorio.ulvr.edu.ec/handle/44000/3626 - Morales Castro, Arturo (2019)
Socially responsible companies have become the screen criteria of investment by investors; they seek to invest in sustainable companies because they see them as generators of long-term value and able to face with economic, financial, social and environmental adversities. However, another of the screen criteria of the investors is the financial health of the companies, with this it is understood that if a company aims to be sustainable it must have healthy finances. Considering a sample of five companies that are listed on the Mexican Stock Exchange of the sector of products of frequent consumption, it is proposed to identify the relationship between socially responsible companies and their financial strength through the time measured with the Z of Altman, to determine This relationship uses the financial statements of companies for the periods of 2009 to 2017. The conclusion reveals that, on average, socially responsible companies show Z ratings above 2.99, which classifies them as financially healthy companies, the case of Bimbo, which in the analyzed period is below 2.99, which classifies it as a company in a danger zone.